The teacher's professional knowledge complexity and training of practical knowledge - Rodríguez Pech, Juanita (2018)
The present essay argues about the complexity of the knowledge implied in the teaching practice, which has been described in literature as diverse because of their content, as well as it’s representation. It is discussed the existent duality between theory and practice as sources of the professional teaching knowledge, as well as the reasons that have been adduced to explain the apparent separation between both of them. It is also presented the teacher practical knowledge as a construct that could represent a way of conciliation between the two, as it allows the reflective integration of different sources of knowledge, into one of apparently more relevance for the teaching practice. Finally, some implications that the development of the practical knowledge has in teacher training are considered.